1981
DOI: 10.1161/01.cir.63.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell damage and thrombus formation after partial arterial constriction: relevance to the role of coronary artery spasm in the pathogenesis of myocardial infarction.

Abstract: SUMMARY The left anterior descending coronary artery of four dogs and the right common carotid artery of 15 rabbits were subjected to 40-60% reduction in transluminal diameter for 1 hour by partial ligation with suture thread. Scanning electron microscopic examination of the luminal surface of these vessels revealed endothelial craters and balloons, fragmentation and desquamation on the proximal slope of the constriction. Platelet attachment to exposed subendothelial tissues was clearly evident, and microthrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(42 citation statements)
references
References 42 publications
2
38
0
2
Order By: Relevance
“…These findings support the suggestion that the threat posed by aneurysm is not limited to the consequences of rupture or hemostatic thrombosis. Rather, aneurysm may result in a compromise of parenchymal (organ) perfusion also as a consequence of endothelial damage which is known to occur in areas of irregular luminal contour as a result of hemodynamic injury (1,20,21). Thrombus formation, regardless of the initiating mechanism, may result in partial or total arterial occlusion at the site ofthe aneurysm or result in occlusion ofsmaller vessels distally following platelet shower or embolization from these sites.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the suggestion that the threat posed by aneurysm is not limited to the consequences of rupture or hemostatic thrombosis. Rather, aneurysm may result in a compromise of parenchymal (organ) perfusion also as a consequence of endothelial damage which is known to occur in areas of irregular luminal contour as a result of hemodynamic injury (1,20,21). Thrombus formation, regardless of the initiating mechanism, may result in partial or total arterial occlusion at the site ofthe aneurysm or result in occlusion ofsmaller vessels distally following platelet shower or embolization from these sites.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Damaged endothelium at the site of Reviews continued focal arterial constriction may serve as a nidus for platelet adhesion and resultant coronary thrombosis. 20 Cocaine causes the release of norepinephrine from adrenergic nerve terminals which has been shown to cause diffuse coronary vasoconstriction of normal human epicardial coronaries both in vitro and in vivo. 21 Two studies have shown that administration of intranasal cocaine results in a significant reduction of coronary diameter as measured by quantitative coronary angiographic analysis.…”
Section: Myocardial Ischemia and Infarctionmentioning
confidence: 99%
“…38 However, the current AHA scientific statement on the management of cocaine-associated chest pain and MI recommends avoiding β-blockers in the acute setting. 34 Since cocaine may directly enhance platelet aggregation and potentiate platelet thromboxane production, and since damaged endothelium at a site of focal arterial constriction may serve as a nidus for platelet adhesion, 16,17,20 antithrombotic and antiplatelet agents are also recommended in managing cocaine-associated MIs. 34 In all causes of aortic dissection, blood pressure control to a target systolic pressure of 110 mm Hg may be achieved using morphine sulfate and intravenous β-blockers.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…No presente caso, encontramos evidências de trombos organizados na microcirculação coronária. Sabe-se que o espasmo coronário pode estar associado a trombose, mesmo em coronárias normais 11 . A cardiopatia isquêmica originou insuficiência cardíaca congestiva e na necropsia foram observados congestão passiva crônica hepática e pulmonar, infartos esplênicos cicatrizados e derrames cavitários.…”
Section: Comentáriosunclassified